Design and Construction of Web-Based Budgeting Submission Information System at CV Expressa - Muhammad Hashfi Rafid Muttaqin; Hanifah Permatasari; Dwi Hartanti (Universitas PGRI Adi Buana Surabaya, 2025)
CV Expressa faces problems in budget management due to a slow manual process, less transparent, and vulnerable to errors. This study aims to design a web -based budgeting information system to improve efficiency and accuracy. System development uses the SDLC Waterfall method (Analysis of Needs, Design, Implementation, Testing, Maintenance) with Laravel Technology (PHP) and PostgreSQL Database. Features include budget submission, tiered approval, reporting, and audit trail. Blackbox testing test results show all functions run optimally, supported by automatic notifications and printed reports. This system is proven to speed up the process, reduce errors, and increase budget transparency at CV Expressa